Pixie and Looking for Meaning: Instructional Manual to Accompany Pixie (Analytic Teaching, 1990)
Introduction:  Pixie, written by Matthew Lipman and edited by Theresa Smith, is a story designed to inspire elementary school students (approximately third grade reading level) to develop inquiring minds and philosophical reasoning abilities.  The accompanying manual, Looking for Meaning by Matthew Lipman and Ann Margaret Sharp, is an extensive and thorough program guide to help the teacher lead students in recognizing and understanding the many relationships portrayed in the Pixie text.  Not only do the program designers present scenarios for introducing and understanding relationships such as metaphors, similes and analogies, but they also urge the users to develop their own abilities toward clearer, more creative thinking and recognition of ambiguities and relationships and to express themselves more clearly in written and oral presentations.